Using tilapia (Oreochromis mosambicus) as a bioindicator to determine mercury (Hg) levels in Lake Taliwang, West Sumbawa Regency 2025 - Sumayyah, Hani; Khairuddin, Khairuddin; Yamin, M. (Jurnal Biologi Tropis, 2025)
Mercury (Hg) is one of the most toxic heavy metals commonly found in aquatic environments, especially in areas affected by illegal gold mining. This study aims to determine the concentration of mercury in the flesh of tilapia (Oreochromis mossambicus) from Lake Rawa Taliwang and assess its safety for consumption based on BPOM Regulation No. 9 of 2022. Tilapia samples were purposively collected from two points around the lake and analyzed using a Mercury Analyzer at a detection wavelength of 253.7 nm. The analysis revealed that the mercury content in tilapia flesh was below 0.5 mg/kg, indicating that it remains within the safe consumption threshold for non-predatory fish. These findings demonstrate the potential of tilapia as a bioindicator for mercury pollution and provide relevant material to enrich environmental education, particularly on the impact of heavy metal contamination in aquatic ecosystems and food safety awareness.